Literacy Analysis of Chemistry Teachers on STEAM (Science, Technology, Engineering, Arts and Mathematics) Learning Approach in Senior High Schools in West Nusa Tenggara Province - Annisah Faujiah Miftahul Jannah; Anti Kolonial Prodjosantoso (Jurnal Penelitian Pendidikan IPA, 2024)
The research was conducted with the following objectives: (1) to determine the literacy ability of chemistry teachers in West Nusa Tenggara Province towards the STEAM leaning approach; (2) knowing the supporting and inhibiting factors of the chemistry teacher's literacy about the STEAM learning approach. The research was conducted at A-accredited Senior High Schools in West Nusa Tenggara Province. The sample selection in this study used a purposive sampling technique with a total of 40 participants in 20 schools. Data collection include open question sheets and interview guidelines. The data analysis technique in this study uses the Miles and Huberman model with data reduction technique, data display, and verification. The result of this study the literacy of state high schools' chemistry teacher in West Nusa Tenggara Province related to the STEAM approach is in the medium category. The supporting factor for the literacy of chemistry teachers in State High Schools in West Nusa Tenggara Province is the existence of professional training and development such as training workshop, MGMP and P4TK. Other supporting factors are professional relationship and the ability to access internet media. The factors that hinder the literacy of chemistry teacher are the lack of training and professional development, the lack of ability to access the internet as an information tool in the search for literature and the limitations of school facilities and infrastructure and time allocation.